(untitled) (LEARNing Landscapes, 2022)
This article spotlights the power of pushing limits and boundaries through emergent curriculum and process drama as told through the story of a preschool class’s exploration of the topics of paths, maps, and pirates. The story is framed in terms of the three phases of the class’s project adapted from the Project Approach (Katz et al., 2014), which started prior to the Coronavirus pandemic, but continued and concluded in the midst of it. Reflections and insight are provided by the classroom teacher including as she drew inspiration from the Reggio Emilia Approach and other professional development and experience.